Essays on high-frequency trading : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Finance at Massey University, Manawatu campus, New Zealand - Zaharudin, Khairul Zharif (Massey University, 2023)
This thesis presents a comprehensive review of the relevant literature on high-frequency trading (HFT). There is no universal definition on HFT to date, leading to inaccurate estimations of their reach and impact in the market. HFT is a specialised form of algorithmic trading with lightning-speed network and implement complex trading strategies. HFT may have both beneficial and harmful effects on the market, and their speed could disrupt the market at remarkable pace. There are several controversies related to HFT, including the 2010 flash crash, social welfare and arms race, and market-making responsibilities. Several initiatives were implemented or proposed as a response to HFT, including speed bumps, price improvement rules, and new trading mechanics to guarantee a fair and orderly market for everyone. The second essay examines the impact of relative tick size on HFT activity. Using data from Australian equity markets, relative tick size is shown to have an inverse relationship with HFT activity. The findings demonstrate that HFTs have a very low tolerance for adverse selection risk, and their risk-averse nature prioritise risk minimisation (order-undercutting) over profit maximisation (order-queuing). The results lend credence to the perception that the primary strategy of HFTs is to generate thin profits while keeping their risk exposure to an absolute minimum. The evidence imply that policymakers may implement a dynamic tick size policy to allocate HFT activity into stocks where it is most required. The third essay illustrates how expected volatility affects HFT activity, and how the resulting change in HFT activity impacts liquidity. Using data from S&P/ASX 200 VIX index (AXVI) to measure sentiment, evidence suggests that when the sentiment is negative: (i) HFTs’ ability to promote trading volume on the ASX is hampered; (ii) HFTs’ ability to reduce spreads on the CHIX is dampened; and (iii) HFTs’ ability to reduce price impact is amplified on both markets. Overall, HFTs’ presence may significantly reduce excessive price impacts when the market is fearful. Therefore, any attempt to completely ban or restrict HFT in the market might accidentally eliminate valuable market participants.
Keywords: Electronic trading of securities; Program trading (Securities); Investment analysis; Algorithms; 350208 Investment and risk management